Innovation Skills and its Utilization among Home Economics Education Graduates of Ahmadu Bello University Zaria, Nigeria - Ahmed, Rakiya; Gaite, Sofia Sal; Salami, Samuel (NIU Journal of Humanities, 2018)
With the increase in the number of graduates searching for work in the labour market, the need for innovation and training in universities and colleges is increasing rapidly. This study examined innovation skills and its utilization among home economics education graduates of Ahmadu Bello University in Zaria Nigeria, where the relationship between innovation skills and its utilization was investigated. The study employed descriptive correlation and cross sectional design. Quantitative approach was also used. Using a purposive and random sampling, 300 staffs of Ahmadu Bello University, local government Administrators, and Home economics graduates from Ahmadu Bello University participated in the study. The data were analyzed using frequency, percentage, mean and standard deviation. Regression was used to test the effects of all the variables, while Pearsonâ€™s linear correlation analyses were used to test the relationship at 0.01 levels of significances. The findings showed that correlation between innovation skills and utilization among the home economics graduates was positive at 0.000 < 0.01 level of significant.  Innovations emerge as the major predictor of skills utilization, and it is recommended that university administrators and policy makers should re-evaluate the current home economics curriculum to suit the techno-preneurialship global demand, and the home economics graduates need to appreciate the benefits of devoting greater attention to the innovation skills acquired and utilized it practically for socio economic development for themselves, their families and the society at large.